2012
DOI: 10.1007/s10195-012-0189-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and functional outcomes of the saddle prosthesis

Abstract: BackgroundThe implantation of a saddle prosthesis after resection of a pelvic tumor has been proposed as a simple method of reconstruction that provides good stability and reduces the surgical time, thus limits the onset of intraoperative complications. There are no studies in the literature of patients evaluated using gait analysis after being implanted with a saddle prosthesis. The present study is a retrospective case review aimed at illustrating long-term clinical and functional findings in tumor patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 22 publications
0
21
0
3
Order By: Relevance
“…29 High complication rates have been reported with the use of various types of endoprosthetic reconstruction because of difficulty in achieving adequate initial fixation and reliable bone ingrowth. 13,14,[30][31][32] This precludes the use of these implants in patients needing a P1/2 resection. Menendez et al 11 reported a 56% incidence of major complications and 60% five-year implant survivorship with the use of the periacetabular reconstruction (PAR) endoprosthesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 High complication rates have been reported with the use of various types of endoprosthetic reconstruction because of difficulty in achieving adequate initial fixation and reliable bone ingrowth. 13,14,[30][31][32] This precludes the use of these implants in patients needing a P1/2 resection. Menendez et al 11 reported a 56% incidence of major complications and 60% five-year implant survivorship with the use of the periacetabular reconstruction (PAR) endoprosthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Menendez et al 11 reported a 56% incidence of major complications and 60% five-year implant survivorship with the use of the periacetabular reconstruction (PAR) endoprosthesis. There have been several reports on the outcome of the use of the saddle prosthesis in periacetabular tumours: the major reported complications were infection (16.7% to 26.7%), periprosthetic fracture (13.3% to 22.2%), and dislocation (18.8% to 22.2%), 1,30,31,33,34 with the patients having a mean MSTS functional score of 50.8% to 57%. However, the implant survivorship was poor being 33.3% at five years.…”
Section: Discussionmentioning
confidence: 99%
“…Все они характеризуются достаточно высокой частотой развития осложнений и неоднозначными функ-циональными результатами после операции. По мнению большинства специалистов, занимающихся реконструк-тивной онкохирургией тазового кольца, универсальной методики реконструкции параацетабулярной области при опухолевом поражении в настоящее время не существует [1,15,18,21,34,35,[47][48][49]. Анализ данных литературы свидетельствует об актуальности обсуждаемой проблемы и перспективности совершенствования имеющихся и разработки новых методик органосохраняющего лечения этих пациентов.…”
Section: заключениеunclassified
“…Однако, несмотря на объективные успехи развития реконструктивной хирургии в онкологической ортопедии, эти операции до сих пор остаются трудоем-кими и сложными оперативными вмешательствами, ха-рактеризующимися значительной продолжительностью, выраженной кровопотерей, длительной послеоперацион-ной реабилитацией и высокой частотой послеоперацион-ных осложнений [15,16]. При этом большинство специ-алистов тазовой онкохирургии считают, что нарушение непрерывности тазового кольца после удаления опухоли в области вертлужной впадины, подвздошных костей и крестцово-подвздошного сочленения требует выполне-ния реконструкции.…”
unclassified
“…Limb salvage following periacetabular resection has evolved over recent years due to the growing availability of reconstructive options. Numerous studies have investigated the types of reconstruction, with options including hip transposition, [1][2][3][4] allografts, [5][6][7][8][9][10] saddle prostheses, [11][12][13][14][15][16][17] modular and custom prostheses, 11,[18][19][20][21][22] as well resection without reconstruction (resection arthroplasty), 2,[23][24][25][26][27] and amputation. 1,3,14,23,28 Resection arthroplasty on is associated with low complication and recurrence rates.…”
Section: Introductionmentioning
confidence: 99%